Highly active electrolytes for rechargeable Mg batteries based on a [Mg2(μ-Cl)2]2+ cation complex in dimethoxyethane1. Issue 20 (28th May 2015) - Cheng, Yingwen; Stolley, Ryan M.; Han, Kee Sung; Shao, Yuyan; Arey, Bruce W.; Washton, Nancy M.; Mueller, Karl T.; Helm, Monte L.; Sprenkle, Vincent L.; Liu, Jun; Li, Guosheng
<x xml:space="preserve">Abstract</x> A novel [Mg2(μ-Cl)2]2+ cation complex, which is highly active for reversible Mg electrodeposition, was identified for the first time in this work.